Isolation, identification and susceptibility pattern of Gardnerella vaginalis in bacterial vaginosis (Bangladesh Journal of Medical Microbiology, 2013)
Bacterial vaginosis is the commonest cause of abnormal vaginal discharge in women of reproductive age. A total 200 women aged 15- 45 years with history of abnormal vaginal discharge were included as study population. Fifty women without such history of discharge were taken as healthy control. Two vaginal swab samples were taken from each case and control. These swab samples were subjected to test by Gram stain (Nugent method) and culture. 21.5 % of the cases were diagnosed as bacterial vaginosis by Gram stain (Nugent method) and 21 % by culture. Clindamycin was susceptible to G. vaginalis in (90.5%) followed by metronidazol (76.1 %), chloramphenicol (71.4 %) and erythromycin (66.7 %). Out of 50 cases of recurrent bacterial vaginosis, G. vaginalis was isolated from 15 (30 %) cases, of which 5 (33.3 %) were sensitive and 10 (66.7 %) were resistant to metronidazol, while all 15 cases were sensitive to clindamycin.DOI: http://dx.doi.org/10.3329/bjmm.v5i1.15814 Bangladesh J Med Microbiol 2011; 05 (01): 8-11